Association between Grade of Normoalbuminuria and Left Ventricular Diastolic Dysfunction (LVDD) in Hypertensive Population of Gunungsari Village, Pamijahan-Bogor, Indonesia - Nur Zamiatun Qomara; Nani Hersunarti B; Anwar Santoso (Jurnal Kardiologi Indonesia, 2019)
Association between Grade of Normoalbuminuria and Left Ventricular Diastolic Dysfunction (LVDD) in Hypertensive Population of Gunungsari Village, Pamijahan-Bogor, Indonesia Nur Z Qomara MD, Nani Hersunarti MD, Anwar Santoso MDDepartement of Cardiology and Vascular Medicine Faculty of Universitas Indonesia  ABSTRACT  Background: Albuminuria has been considered an important diagnostic marker of decreasing renal function, but lately albuminuria has also been linked to cardiovascular and peripheral vascular disease. Many studies have analyzed the association between micro- or macroalbuminuria and the increased risk of cardiovascular disease, but only few examined the association between normoalbuminuria and cardiovascular disease.Objective: To analyze the association between the degree of normoalbuminuria and the occurrence of left ventricular diastolic dysfunction in hypertensive patients.Method: This is cross-sectional analysis in hypertensive patients. Normoalbuminuric subjects are divided into three tertiles based on the cutoff of Urine-Albumin-Creatinine Ratio (UACR). To evaluate left ventricular function, all subjects undergo echocardiography examination. Left ventricular diastolic dysfunction is positive if more than fifty percent of positive findings are present from the fourth parameters stated in the 2016 American Society of Echocardiography criterias.Results: No significant difference in the occurrence of LVDD was found between the two groups according to age, sex, smoking, dyslipidemia, physical activity, BMI, hypertension therapy and HbA1c, but a significant difference was seen in the UACR tertile of the two group. This study showed that upper-limit normoalbuminuria (third tertile) was associated with the occurrence of LVDD (OR 15.57, 95% CI: 2.88-84.25).Conclusion: This study showed that normoalbuminuria in hypertensive population is associated with left ventricular diastolic dysfunction. Keywords: hypertension, normoalbuminuria, left ventricular diastolic dysfunctio